Typing of leptospiral serovars by DNA restriction enzyme analysis - KUMAR, A SENTHIL; RAMADASS, P; NACHIMUTHU, K (The Indian Journal of Animal Sciences, 2013)
DNA restriction endonucleases have been used for characterizing the various leptospiral serovars. Reference strains (13) and rat isolate RI were selected for this study. DNA samples were prepared and subjected to restriction enzyme analysis with different enzymes. Complete digestion of the samples was obtained with Bam HI, Eco RI, Hae III, Hha I and Hind III: The enzymes Hae III and Hha I produced good resolution, among the patterns produced by the enzyme Hae III facilitated clear differentiation between different serovars. The rat isolate RI restriction enzyme map was similar in pattern with the reference strain Veldrat Batavia 46 of the serovarjavanica.